2021
DOI: 10.1007/s10072-021-05398-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s point of view on the use of telemedicine in multiple sclerosis: a web-based survey

Abstract: Restrictions in the access to healthcare facilities during COVID-19 pandemic have raised the need for remote monitoring of chronic medical conditions, including multiple sclerosis (MS). In order to enable the continuity of care in these circumstances, many telemedicine applications are currently tested. While physicians’ preferences are commonly investigated, data regarding the patients’ point of view are still lacking. We built a 37 items web-based survey exploring patients’ propensity, awareness, and opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…A survey conducted at an MS Center in Italy found that only higher levels of education and income were associated with interest in telemedicine, but not characteristics of MS such as mobility. 18 These findings are similar to those in the general population. Of 148,402 patients attending primary care or specialty ambulatory care visits, only 54.4% completed a telehealth visit, of which 45.6% were video visits.…”
Section: Discussionsupporting
confidence: 84%
“…A survey conducted at an MS Center in Italy found that only higher levels of education and income were associated with interest in telemedicine, but not characteristics of MS such as mobility. 18 These findings are similar to those in the general population. Of 148,402 patients attending primary care or specialty ambulatory care visits, only 54.4% completed a telehealth visit, of which 45.6% were video visits.…”
Section: Discussionsupporting
confidence: 84%
“…The use of telemedicine appointments and digital tools in clinical settings has increased in recent years, mainly due to the coronavirus disease (COVID-19) pandemic [ 58 , 59 ]. In a recent survey of 613 patients with MS, 54% stated that they would be open to telemedicine appointments with neurologists and an unmet need for digital tools tailored to patients with MS was highlighted [ 60 ]. As MSProDiscuss is web-based, it was tested during the COVID-19 pandemic and showed promise in assisting with remote visits in which lack of face-to-face interaction can be a barrier to HCP–patient communication [ 40 ].…”
Section: Future Applications Of New Technologies In Msmentioning
confidence: 99%
“…6,9 For example, telemedicine can decrease the time before people with MS can access specialized heath care services (eg, neurologic rehabilitation experts) compared with standard in-person care. 10,11 Televideo-enabled neurologic care for patients with MS decreases travel time, 12,13 limits time off work, 12,14 reduces caregiver burden, 4,12 Once published in an issue, the paper will be removed from the Online First section and appear in that issue's table of contents. Meanwhile, the manuscript is citable using the DOI, which appears on the first page.…”
Section: Introductionmentioning
confidence: 99%